Extracapsular dissection for Warthin tumor in the tail of parotid gland. (2nd September 2017) - Lee, Dong Hoon; Yoon, Tae Mi; Lee, Joon Kyoo; Lim, Sang Chul
Abstract: Conclusions: Extracapsular dissection conferred the advantage of reduced operation time and morbidity without any recurrence, and it could be considered as the treatment of choice for Warthin tumors in the tail of the parotid gland. Objective: The purpose of this study is to confirm the appropriate surgical procedure for Warthin tumor in the tail of the parotid gland, by comparing the results of extracapsular dissection and superficial parotidectomy. Materials and methods: The medical records of 72 patients with Warthin tumor in the tail of the parotid gland who underwent surgery between January 2006 and December 2016 were retrospectively reviewed. Results: In the extracapsular dissection group, a total of 44 parotid gland operations were performed in 40 patients. In the superficial parotidectomy group, a total of 34 parotid gland operations were performed in 32 patients. The operation time was significantly shorter in the extracapsular dissection group than in the superficial parotidectomy group ( p <.001, Table 1). One patient in the extracapsular dissection group and five patients in the superficial parotidectomy group had postoperative facial nerve palsy. Recurrence of Warthin tumor in the tail portion of the parotid gland was identified in one patient who underwent superficial parotidectomy.